Providing the corporate security strategy in the management system of the enterprise - Taras Shyra; Oleksandr Shtyrov; Ivan Korchynskyy; Anastasiia Zerkal; Halyna Skoryk (Verslas: Teorija ir praktika / Business: Theory and Practice, 2020)
Three basic variants of the strategy for ensuring corporate security of an industrial enterprise ('survival', 'stabilization' and 'support') are proposed, the choice of one of which is associated with the results of assessing the level of corporate security. By applying the hierarchy analysis method for one of the studied enterprises, threats were identified that can have the most significant impact on the implementation of the basic strategy, therefore, they require the use of appropriate tactical countermeasures and make it possible to achieve strategic goals. Article theoretically generalizes and resolves the scientific and practical problem, which consists in developing the theoretical and methodological foundations for ensuring corporate security in the context of countering external and internal threats. In the process of research, methods of expert evaluation were used, as well as hierarchical ordering methodologies together with the use of a matrix of pairwise comparisons. It is substantiated that in conditions of high dynamics of changes in the environment of enterprise functioning, there is a need to predict changes in the influence of threats (strengthening, unchanged, weakening), combined into the groups 'internal' and 'external'. The calculations carried out provided the formation of the necessary information basis for planning and implementing tactical protective measures based on the increased influence in the conditions of the functioning of enterprises in Eastern Europe, these are precisely internal threats. The value of this study lies in the fact that such a system for assessing external and internal threats that affect the corporate security of industrial enterprises will allow to quickly and efficiently form a system to counter the impact of these threats.
Keywords: M14; G34; P42; L21; 650; corporate security; threat; enterprise; matrix of paired comparisons; scenario; hierarchy